2011
DOI: 10.1007/s10551-011-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be Job Ready: Strategies for Greater Social Inclusion in Public Sector Employment

Abstract: Learning to be job ready' (L2BJR) was a pilot scheme involving 16 long-term unemployed people from a range of backgrounds being offered a 6-month paid placement within the care department of a city council in Northern England. The project was based on a partnership with the largest college in the city specialising in post-16 education and training for residents and employees. The college targeted people as potential candidates for the programme through their prior attendance on or interest in care courses at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Several studies show that the employment of PWD leads to an increase in creativity (Gröschl, 2007;Dibben et al, 2002), better decision-making processes (Dibben et al, 2002), improved ability to solve problems in companies (Lindsay et al, 2018) and stimulated innovations facilitated through the associated diversity in the teams (ODEP, 2009). PWD themselves are often innovative and creative in how they work with their clients (Bennett, 2011) and seem to have a positive impact on service quality and efficiency (Lindsay et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that the employment of PWD leads to an increase in creativity (Gröschl, 2007;Dibben et al, 2002), better decision-making processes (Dibben et al, 2002), improved ability to solve problems in companies (Lindsay et al, 2018) and stimulated innovations facilitated through the associated diversity in the teams (ODEP, 2009). PWD themselves are often innovative and creative in how they work with their clients (Bennett, 2011) and seem to have a positive impact on service quality and efficiency (Lindsay et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Some companies operate sheltered work centers or other separate employment opportunities for PWD or regularly place orders in sheltered work centers to promote the employment of PWD (Segovia-San-Juan, Saavedra and Fernández-de-Tejada, 2017). The idea of promoting social inclusion through CSR is largely absent in the literature, and there is only little empirical research on the concept and practice of CSR regarding social inclusion (Bennett, 2011). Also, the employment of PWD has so far received only little attention in the literature on CSR (Csillag, Gyori and Matolay, 2018; Pérez, Romeo and Yepes-Baldó, 2018; Markel and Barclay, 2009).…”
mentioning
confidence: 99%
“…This can be done through training and placement programs for PWD in entry-level positions (Sherbin & Kennedy, 2017). PWD can be made fit for work and return to the labor market after a long period of unemployment or disability by means of a temporary job or internship (Bennett, 2011). Internships and other employment opportunities are also important for graduates with disabilities to get started quickly (Kuznetsova, 2012).…”
Section: Variants Of Implementation Of the Csr Initiative To Promote mentioning
confidence: 99%
“…The exclusion of disadvantaged groups from the value chain can be seen as a waste of resources on an individual, entrepreneurial, national and global level (Dyda, 2008). This is illustrated by the importance of both supply and demand factors (Crisp et al, 2009) in addressing unemployment and social inclusion issues of PWD (Bennett, 2011). It might be concluded that companies need legal regulations and monetary incentives to take responsibility for employing PWD (Győri & Ócsai, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation